LOW METABOLIC RATES IN SALAMANDERS ARE CORRELATED WITH WEAK SELECTIVE CONSTRAINTS ON MITOCHONDRIAL GENES. (16th November 2012) - Chong, Rebecca A.; Mueller, Rachel Lockridge
<x xml:space="preserve">Abstract</x> Mitochondria are the site for the citric acid cycle and oxidative phosphorylation (OXPHOS), the final steps of ATP synthesis via cellular respiration. Each mitochondrion contains its own genome; in vertebrates, this is a small, circular DNA molecule that encodes 13 subunits of the multiprotein OXPHOS electron transport complexes. Vertebrate lineages vary dramatically in metabolic rates; thus, functional constraints on mitochondrial‐encoded proteins likely differ, potentially impacting mitochondrial genome evolution. Here, we examine mitochondrial genome evolution in salamanders, which have the lowest metabolic requirements among tetrapods. We show that salamanders experience weaker purifying selection on protein‐coding sequences than do frogs, a comparable amphibian clade with higher metabolic rates. In contrast, we find no evidence for weaker selection against mitochondrial genome expansion in salamanders. Together, these results suggest that different aspects of mitochondrial genome evolution (i.e., nucleotide substitution, accumulation of noncoding sequences) are differently affected by metabolic variation across tetrapod lineages.